2014
DOI: 10.1007/s00330-014-3114-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body MRI for initial staging of paediatric lymphoma: prospective comparison to an FDG-PET/CT-based reference standard

Abstract: • Accurate staging is important for treatment planning and assessing prognosis • Whole-body MRI-DWI could be a good radiation-free alternative to FDG-PET/CT • Interobserver agreement of whole-body MRI-DWI is good • Agreement between whole-body MRI and the FDG-PET/CT reference standard is good • Most discrepancies were caused by suboptimal accuracy of size measurements on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 33 publications
5
73
0
2
Order By: Relevance
“…Diffusion-weighted MR imaging is sensitive for detecting lymph node involvement, represented by bright round-to-ovoid lesions larger than 10 mm in size with restricted diffusion (Fig 19c) (117). Whole-body diffusion-weighted imaging has been shown in preliminary studies to be feasible and comparable to FDG PET/CT for initial staging (117).…”
Section: Sporadic Burkitt Lymphomamentioning
confidence: 98%
“…Diffusion-weighted MR imaging is sensitive for detecting lymph node involvement, represented by bright round-to-ovoid lesions larger than 10 mm in size with restricted diffusion (Fig 19c) (117). Whole-body diffusion-weighted imaging has been shown in preliminary studies to be feasible and comparable to FDG PET/CT for initial staging (117).…”
Section: Sporadic Burkitt Lymphomamentioning
confidence: 98%
“…The emerging role of whole-body magnetic resonance imaging for disease monitoring in NHL Over the last years, several studies have demonstrated the good reliability of whole-body magnetic resonance imaging (WB-MRI) for lymphoma staging, mainly using 18 F-FDG-PET/CT as the reference standard [24][25][26][27]. WB-MRI enables avoiding radiation exposure and intravenous contrast agent administration, allowing the evaluation of all potential lymphomatous sites through morphological and functional sequences ( Figs.…”
Section: Imaging Monitoring and Wwmentioning
confidence: 99%
“…30 Interestingly, some studies pointed out that DWI may lead to clinically relevant overstaging. [31][32][33] Quarles van Ufford et al 32 concluded that large-scale studies are needed to prove that DWI leads to correct staging compared with PET/CT.…”
Section: Pet/ct and Pet/mr For Initial Stagingmentioning
confidence: 97%